Safety formats for non-linear finite element analysis of reinforced concrete structures: discussion, comparison and proposals. (15th August 2019) - Castaldo, Paolo; Gino, Diego; Mancini, Giuseppe
Highlights: Safety formats for NLFEAs of reinforced concrete structures are analyzed. NLFEAs to assess global resistance of reinforced concrete members are performed. Different reinforced concrete members with different failure modes are considered. A proposal of two preliminary NLFEAs to use safety formats is presented. Failure mode-based safety factor for aleatory uncertainties is proposed. Abstract: The study describes some proposals regarding the safety formats (i.e., global resistance methods (GRMs) and probabilistic method (PM)) for non-linear finite element analysis within the approach of the global resistance format to estimate the design strength of reinforced concrete structures. Specifically, non-linear finite element models are properly defined to reproduce various experimental tests. Successively, several non-linear finite element analyses are carried out in compliance with the different safety formats for each reinforced concrete structure experimentally tested in order to compare and critically discuss the results in terms of resistance and failure mode. In fact, the different safety formats are investigated to demonstrate if they are able to estimate the corresponding design global resistance capacities and to capture any possible modification in the failure mode for each structure considering the aleatory uncertainties. Then, a methodology based on a specific preliminary evaluation, composed of two non-linear finite element analyses, is proposed to verify the applicability of the simplified GRMs depending on the possible modifications that can occur in the failure mode in comparison with the PM taking into account the aleatory uncertainty on the materials properties. Moreover, in the cases when any GRM cannot be used, the PM is suggested as the unique safety format able to estimate an appropriate value of the global design structural resistance due to the possible modifications in the structural response by the effect of combination of the actual materials strengths. Finally, in order to apply GRMs for their reduced computational effort also in the abovementioned cases, an additional failure mode-based safety factor is proposed for the assessment of the design global resistance.